Effect of Different Layers on the Performance of Laminate Epoxy Composite Reinforced with Textile Waste - Thomas Junaedi; Januar Parlaungan Siregar; Mohamed Reza Zalani; Al Ichlas Imran; Tezara Cionita; Endah Murtiana Sari; Deni Fajar Fitriyana; Etanto Heiliano Wijayanto (Advance Sustainable Science Engineering and Technology, 2026)
Post-consumer textile waste poses significant environmental problems, but its potential for commercial recycling remains under-researched. Therefore, this study utilizes calico textile (CT) waste as reinforcement in polymer composites. The effect of layering number of CT in epoxy composite will be investigated. CT was varied with three layers, namely 1, 3, and 5 embedded in epoxy resin with the hand lay-up method in open molding. The mechanical testing of pure epoxy as a control point for tensile, flexural, and impact strengths of 13.68 MPa, 16.44 MPa, and 0.013 J/mm². In tensile strength, the increase occurred in CT1 and CT3 by 21% and 39.7%, A significant rise of 43.5% occurred in the CT5 flexural test, and impact strength saw a significant jump from CT1 to CT3 by 58%. Overall, observations of the composite laminar tensile fracture morphology indicate that the longitudinal loading effectively increases the tensile strength. However, void bubbles were found between the textile layers, but this condition does not contribute a significant reduces the mechanical performance. Further research is recommended using the synthetic fabric waste as a reinforcement composite.